Plexiform neurofibromas of bilateral brachial and lumbosacral plexuses - S Sheetal; S Vijayalekshmi; Aswathy Sasidharan; N Jisa Merin Joy (Apollo Medicine)
Plexiform neurofibroma is a peripheral nerve sheath tumor that involves multiple nerve fascicles or nerve branches and is considered to be pathognomic of neurofibromatosis type-1. They are often large lesions which can distort the nerves and are most commonly reported in the craniomaxillofacial region. We are reporting plexiform neurofibroma of bilateral brachial and lumbosacral plexuses, which is rarely reported, with only three cases being reported so far. A 33-year-old woman presented with complaints of dragging of the right lower limb on walking, for the past 6 months and on examination, was noted to have features of cervical myelopathy. Magnetic resonance imaging of the spine showed multiple lesions of the cervical exiting nerve roots bilaterally, with extension along the brachial plexus and lesions along the lumbar plexus on both sides suggestive of plexiform neurofibroma. Considering the lack of feasibility of complete resection, surgery was not considered and she was advised to be under follow-up. Plexiform neurofibromas are large lesions arising from peripheral nerves and can cause symptoms due to the compression of adjacent structures. Plexiform neurofibroma involving brachial and lumbosacral plexuses on both sides is very rarely reported, with only three cases being reported so far.